Noticeable improvement in the toxic gas-sensing activity of the Zn-doped TiO2 films for sensing devices. (26th May 2021) - Krishnan, V. Gopala; Elango, P.; Ravikumar, K.; Marnadu, R.; Aldossary, Omar M.; Ubaidullah, Mohd
Abstract : Sensing element view, sening mechanism, stability, response and recovery time of the Zn-doped TiO2  films. Abstract : Zn-doped TiO2 films were deposited on ultrasonically treated alumina substrates via the automatic nebulizer spray pyrolysis method. In this study, the thickness of the as-prepared films was gradually reduced, and their Brunauer–Emmett–Teller (BET) surface area and pore volume results were notably improved; in addition, values for the blue-shifted sharp edge absorption with an enlarged bandgap ( E g ) were revealed in the deposited films. The agglomerated granular form has evolved into tiny grains with porous brighter particles scattered over the surface of the coated films. The sensing performance to reducing gases for combustible gas of ammonia (NH3 ) and volatile organic compounds of methanol (CH4 O) and formaldehyde (HCHO) with the function of operating temperature and gas concentration were studied, and the highest sensing response of the hazardous formaldehyde (HCHO) reducing gas was noticed.